La Conciliación en materia de tránsito a la luz del principio de igualdad formal - Haro Mariño, Carla Johana (2023)
ABSTRACT: The reasonable doubt that is generated about the constitutionality of the rule relates to the provisions of Art. 8 of Resolution No. 327-2014, issued by the Plenary Session of the Judicial Council, which regulates the Regulations for conciliation. regarding traffic violations, and develops conciliation in the direct process, which recognizes that, according to the procedure determined in Art. 640 of the Comprehensive Organic Penal Code, conciliation will only operate with respect to the conditional suspension of the sentence and in no case In this case, the jurisdictional decision to reduce points will be suspended. This article would be affecting the principle of formal equality. The quantitative approach to legal research is a study method that focuses on collecting data and researching primary sources to reach conclusions based on the information collected. This information is collected by conducting surveys, interviews and document analysis. This data is analyzed to reveal patterns, trends, and relationships between variables. These patterns and trends can then be used to predict the outcomes of a case or to establish relationships between legal concepts. It is concluded that conciliation is an extrajudicial method that allows reaching an agreement between the parties involved in a judicial process without the need to resort to a trial. This figure is based on principles such as voluntariness, confidentiality, flexibility, neutrality, impartiality, equity, legality and honesty. In case of transit, even if the crimes are culpable, conciliation is prohibited in the event that the damage refers to legal rights such as the Right to life. Keywords: conciliation, transit, principles, formal equality, crimes and reasonable doubt